Informal Caregivers in Care Efficiency - Charalambous, Andreas (My University, 2023)
Although the exact economic impact of cancer and other noncommunicable diseases is not completely understood, there is little doubt that the impact is immense. Due to premature death and disability, about $895 billion of economic impact was debited in 2008 globally without including the direct medical cost, which could further increase the financial lost. Healthcare expenditures for cancer have systematically increased significantly and are projected to increase further over the next decade. In the midst of such a financial impact, healthcare systems have introduced system-based changes as a response to increasing efficiency. These changes have also resulted in more responsibilities being placed on informal caregivers. The chapter provides an overview of the concept of efficiency not only in the wider healthcare context but also in the specific context of cancer. The chapter thoroughly discusses informal caregivers as drivers of efficiency, highlighting their potential to provide patient-center care and improve health outcomes through their role.
Keywords: Efficiency; Person-centered care; Health context; Informal caregivers